2022
DOI: 10.7554/elife.77545
|View full text |Cite
|
Sign up to set email alerts
|

Structural differences in adolescent brains can predict alcohol misuse

Abstract: Alcohol misuse during adolescence (AAM) has been associated with disruptive development of adolescent brains. In this longitudinal machine learning (ML) study, we could predict AAM significantly from brain structure (T1-weighted imaging and DTI) with accuracies of 73 - 78% in the IMAGEN dataset (n ~1182). Our results not only show that structural differences in brain can predict AAM, but also suggests that such differences might precede AAM behavior in the data. We predicted ten phenotypes of AAM at age 22 usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 68 publications
0
24
2
Order By: Relevance
“…Due to significant differences in the number and mean age of female and male patients, we balanced the dataset by separating all patients into groups according to sex and age and then randomly selecting patients within these groups until there were no more significant differences (up to p ≤ 0.1). This was necessary to ensure the predictions of our models were not based on an inherent bias in the training data (e.g., women being older on average and thus having worse outcomes) ( 16 ). The patient selection process is shown in Figure 1 and the characteristics of the dataset are described in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to significant differences in the number and mean age of female and male patients, we balanced the dataset by separating all patients into groups according to sex and age and then randomly selecting patients within these groups until there were no more significant differences (up to p ≤ 0.1). This was necessary to ensure the predictions of our models were not based on an inherent bias in the training data (e.g., women being older on average and thus having worse outcomes) ( 16 ). The patient selection process is shown in Figure 1 and the characteristics of the dataset are described in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…To reduce complexity and potential problems brought on by multiple comparisons, a small set of three ML algorithms were selected. A Support Vector Machine (SVM) with linear kernel (SVM-lin) ( 19 ) and a SVM with radial basis function kernel (SVM-rbf) ( 20 ) were chosen as linear and non-linear models due to their strong performance in previous studies and the ability to directly compare them ( 6 , 16 , 21 ). Similarly, Gradient Boosting (GB) ( 22 ) was chosen as the tree-based classifier due to its superior performance and when compared to other tree-based models ( 23 , 24 ).…”
Section: Methodsmentioning
confidence: 99%
“…In line with this, using a more comprehensive methodological approach, we recently demonstrated that binge drinking at age 22 can be predicted from structural magnetic resonance imaging (sMRI) features at age 14 with an average balanced accuracy of more than 70%. Of note, the number of lifetime binge drinking occasions was the best predictable among multiple phenotypes of alcohol misuse (11).…”
Section: Introductionmentioning
confidence: 97%
“…Achieving this necessitates an understanding of the neuro-psychological predispositions driving risky alcohol consumption during adolescence (8). Several recent studies suggest that differences in adolescent brain structure can predict binge drinking (9)(10)(11). Longitudinal multi-site projects, such as the IMAGEN study (12), provide a unique opportunity to identify neural predictors of binge drinking in a large-scale sample of adolescents (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation